A dictionary of the English Bible and its origins - Gilmore, Alec (Biblical seminar, 2000)
This Dictionary is designed to increase awareness of Bible origins, introduce readers to the variety of versions and manuscripts that lie behind the familiar English translation(s). It also provides, in alphabetical order, 'student notes' on texts, versions, manuscripts, persons, places and terminology, covering the origins of the Hebrew Bible, the New Testament and the English Bible, including recent translations. Generally, this book will facilitate a more intelligent understanding of the Bible among lay people by removing some of the mystique and prejudices associated with it. Entries are f.